Determining Romania's position in Europe according to the optimized Global Food Security Index in 2018 - Cristina N\~aftan\~ail\~a; Odi Mihaela Z\~arnescu; Laurentia Avram; Viorica Braga; Robert Dragomir; Elena Gurgu (Amfiteatru Economic Journal, 2019)
This article aims to analyze how the Global Food Security Index (GFSI) has evolved across the European countries for the period 2012-2018. In this respect, we have taken as a starting point the Report of Global Food Security Index 2018 as well as the scientific literature from the main stream of publications focusing on food security. The data presented were analyzed and presented statistically, on the basis of which we prepared tables relevant to the proposed goal. The aim of this research is to determine the most vulnerable countries in terms of food security. We analyzed the evolution of the Global Food Security Index for the period 2012-2018, and the subcategories of indicators underlying the determination of the overall GFSI index score: food affordability, food availability, food quality and safety. We also looked at the adjustment indicator data used to determine the GFSI index, natural resources and adaptability. The natural resources and adaptive capacity indicator measure the exposure of a country to the impact of a changing climate; its susceptibility to the risks of the natural resources and how a country adapts to these risks. When applied, it acts as an adjustment factor for countries' food security scores. The originality of the paper is to build a globally optimized index for GFSI to provide a comparative analysis of European countries in terms of food security, highlighting Romania's position in this scientific approach. The motivation for calculating the optimized global food security index lies in the fact that it has only sub-indicators contributing to significant achievements, and its refining has gone through mathematical processing that led to a more relevant hierarchy. The indicator categories selected within this article are based on the analysis conducted by the Economist Intelligence Unit, Research Division of The Economist that is the world leader in global business intelligence in the above-mentioned report. On the basis of the analysis we drew conclusions regarding the food security in Romania compared to the European countries.
Keywords: Q11; Q17; Q18; 330; food security; global food security index (GFSI); GFSI optimized global index; food availability; food affordability; natural resources; food quality and security